Government Ownership and Firm Performance: the Case of Vietnam - Tran, Ngo My; Nonneman, Walter; Jorissen, Ann (International Journal of Economics and Financial Issues, 2014)
This study extends some predictions from a game theoretical model which evaluates the net effect of government ownership on firm performance and empirically tests these predictions using a panel data of Vietnamese firms in the period 2004-2012. The empirical results estimated from static and dynamic models confirm our propositions of a negative effect of state ownership on firm profitability and labor productivity. Furthermore, this study documents a moderating role of firm size in the relationship between state shareholding and the performance of firms with higher state ownership in larger firms enhancing profitability and labor productivity. Keywords: government ownership; firm performance; dynamic model and interaction effect JEL Classifications: H11; P27 <!--[endif] -->